النشاطات التبشيرية في إندونيسيا: تداعياتها على المسلمين وموقف المفكِّر محمد ناصر من أساليبها = Christian mission in Indonesia: response of Mohammad Natsir - Solihin, Sohirin Mohammad; Nasser, Youcef (Saida University- Algeria, 2019)
ستعرض هذا البحث نشاطات التبشير المسيحي ومخاطره على المجتمع الإندونيسي المسلم ذي الغالبية السكانية، والذي ما تزال انعكاساته السلبية تلقي بظلالها على الوحدة الوطنية، حيث تفككت إندونيسيا في إنسانها وجزرها لأسباب دينية في الغالب. كما بسطنا في هذا البحث مخاوف المفكِّر الإندونيسي محمد ناصر وتحذيراته لحكومة سوهارتو من تداعيات توسُّع التبشير المسيحي بأشكال خفية وغير قانونية في ظل رضا الغرب الليبرالي المتوحش عن سوهارتو الذي كان يغض بصره عن التبشير المسيحي غير القانوني والمرفوض من الإندونيسين المسلمين. ******************************************************* The paper exposes the danger threat of Christian mission in Indonesian Muslim community that represent largest population of the country. It brings negative impact on national stability and disunite people due to such kind of religious activity. Moreover, it also describes the fear of Indonesian Muslim thinker, Mohammad Natsir, who vehemently criticized against Suharto’s policy to support hidden Christian missionary activities to comply with liberal thought of West at the time when he was heedless to hear the protest from Muslim masses.